Tradisi Marhata Sinamot dalam Adat Perkawinan Batak Toba: Kajian Sosiologi Agama dan Pandangan Gereja Katolik - Yanto Sandy Tjang; Herkulana Mekarryani Soeryamassoka; Yosephin Metauli Situmorang; Vensius Rico Novi Andry; Theresia Lina Iswaraningsih; Victoria Julianti Siska Ubeq (Borneo Review, 2025)
This study examines the meaning and function of the Marhata Sinamot tradition in Batak Toba customary marriage and its relationship with Catholic teaching within the framework of the sociology of religion. Using a qualitative-descriptive approach through literature study, it draws on the thought of Durkheim, Weber, Marx, and Berger, as well as Church documents on inculturation. The findings show that Marhata Sinamot functions as a rite that reinforces social integration and kinship cohesion (Durkheim), and reflects actions driven by moral values and family social status (Weber). From Marx’s perspective, sinamot maintains economic relations and resource distribution patterns, while Berger highlights its role in shaping the social construction of reality that provides symbolic legitimacy to kinship structures. Although recognizing positive values such as respect for women’s dignity, family responsibility, and social solidarity, the Catholic Church emphasizes that sinamot does not determine the validity of the sacrament of marriage. The study concludes that Marhata Sinamot remains culturally and religiously relevant when practiced proportionally in line with Church teaching. Recommendations include pre-marital catechesis, dialogue with customary leaders, inculturated liturgical guidelines, and family economic empowerment to support faith formation and the preservation of Batak Toba cultural identity in modern society.